Characteristics of Small Farm Operators in Florida: Economics, Demographics, and Preferred Information Channels and Sources - Steven A. Gaul; Robert C. Hochmuth; Glenn D. Israel; Danielle Treadwell (EDIS, 2009)
WC088, an 11-page illustrated report by Steven A. Gaul, Robert C. Hochmuth, Glenn D. Israel, and Danielle Treadwell, summarizes the results from the 2008 University of Florida IFAS Extension–Florida Agricultural and Mechanical University (FAMU) Small Farm Survey. This information can then be used by Extension faculty to identify target audiences, develop relevant materials, and deliver this information through appropriate channels to assist farmers in achieving the goals of their small farm enterprises. Includes references. Published by the UF Department of Agricultural Education and Communication, July 2009.